Quality assessment of eggs packed under modified atmosphere - Giampietro-Ganeco, Aline [UNESP] (2015)
Eggs are perishable foods and lose quality quickly if not stored properly. From the moment of posture to the marketing of egg, quality loss occurs through gas exchange and water through the pores of the shell with the external environment and thus, studies involving modified atmosphere packaging are extremely important. The aim of the present study is to assess the internal quality of eggs packed under modified atmosphere and stored at room temperature. Six hundred and twelve fresh commercial eggs from 38-week old Hisex White laying hens were used. The present study was conducted in a completely randomized experimental design in a 4 x 4 + 1 factorial arrangement [vacuum, vacuum with oxygen gas (O-2) absorbent, vacuum with oxygen gas (O-2) and carbon dioxide (CO2) absorbents, vacuum with oxygen gas (O-2) absorbent and carbon dioxide (CO2) gas generator; storage times (7, 14, 21 and 28 days), control group (fresh eggs)], with three repetitions (12 eggs each). The following factors were assessed: weight maintenance during storage; Haugh unit; color and yolk index. The modified atmosphere packaging maintained the weight of the eggs during a period of 28 days. Vacuum packaging with O-2 absorbent and CO2 gas generator was more efficient in maintenance of egg quality, based on the values of Haugh unit and yolk index. The luminosity of the yolk was preserved during the 28 storage days in all of the packaging types used. The vacuum packaging with O-2 gas absorbent and CO2 gas generator provide an increase in internal egg quality.